STRATEGI PEMASARAN PADA INDUSTRI PERHOTELAN - DENNY FARABI (Media Bisnis, 2014)
The purpose of research is to analyze whether a marketing strategy used by management Quality Hotel Yogyakarta has been in accordance with the business development and changing market conditions. SWOT analysis showed that the difference in weight strength with weakness Quality Hotel Yogyakarta has a value of +0.84. While the difference in opportunities with threats to have a value of +0.40 This means the position of Quality Hotel Yogyakarta on the SWOT matrix is in quadrant I with the description of the hotel faces several environmental opportunities and have the forces that encourage to take advantage of those opportunities. Situations like this require Quality Hotel Yogyakarta take growth oriented strategy.